Evaluation of microalgae’s (Chlorella sp. and Synechocystis sp.) pollutant removal property: Pig effluent as a live stock discharge - Leonidas Pachacama & , Juan Ortiz Tirado, Jessica Duchicela, Bangeppagari Manjunatha, Rajesh R. Kundapur, Bugude Rajeswari (Journal of Applied Pharmaceutical Science, 2016)
The ability of microalgae to remove nitrogen and phosphorus from wastewater has been used in recent years as an alternative treatment for discharges from livestock slurry, which generate a negative environmental impact on vulnerable ecosystems. With this background and the feasibility of using microalgae, we have evaluated the effect of Chlorella sp. and Synechocystis sp., in removing contaminants from the pig manure collected from El Prado ESPE. Slurry samples were collected, filtered and autoclaved, and the supernatant was further diluted to three different concentrations of 40%, 60% and 80%. The microalgal growth and pollutants removal property was evaluated up to 15 days in batch culture. The cell density was determined by counting in a Neubauer hemocytometer, and the pollutants removal was analyzed by standard colorimetric methods. The microalgae Chlorella sp. showed a maximum cell growth of 1.70 ± 0.09 x107 cells/mL at 60% effluent concentration on day 6. While Synechocystis sp. showed a maximum growth of 1.04 ± 0.05 x107 cells/mL, at 60% concentration on day 9. On the other hand, there exists a competition when microalgae used as a consortium. The cell growth of Chlorella sp. was higher at all concentrations compared to Synechocystis sp.. Overall, efficiency of pollutant removal were between 40% and 90%, which demonstrate the feasibility of using microalgae in tertiary swine wastewater treatment.
Keywords: Chlorella sp., Synechocystis sp., nitrogen, phosphorus, wastewater.